ANALISIS DAMPAK REDEMPTION MOMENT TERHADAP NET ASSET VALUE PER UNIT DAN NEW NET CASH FLOW PADA UNIT TRUST SYARIAH DAN UNIT TRUST KONVENSIONAL (STUDI KASUS PADA UNIT TRUST SYARIAH DAN UNIT TRUST KONVENSIONAL YANG TERCATAT AKTIF DI BADAN PENGAWAS PASAR MODAL) - Eka Frieda Merdekawati; Bambang Agus Pramuka; Krisnhoe Rachmi Fitrijati (Universitas Semarang, 2020)
Redemption moment which was happened in the beginning of 2005 gave a worse effect for national unit trust industry in Indonesia. Wave of redemption was attacked most of fixed income unit trust products. The return of conventional fixed income unit trusts portofolio which was invested in government bond and coorporate bond had decreased drasctically. When conventional fixed income unit trusts had lost almost their fund, sharia fixed income unit trusts were success collecting amount of fund from their investor.Analysis the effect of redemption moment use Net Asset Value per Unit as the unit trust indicator ofinvestment perfomance quality and New Net Cash Flow as an indicator the quality of liquidity for the unit trust management company. Through Net Asset Value per Unit and New Net Cash Flow, we can indirectly compare the quality of investment perfomance and the quality of liquidity between shariaand conventional fixed income unit trust before and after redemption moment periods.The central tendency analysis (mean) and t-test for pair sample have been used on this research.; Results of this research shown that no significant differences between sharia and conventional fixed income unit trust's Net Asset Value per Unit and New Net Cash Flow before and after redemption moment periods. It reflected that sharia fixed income unit trust's investment perfomance become stable and the liquidity become capable. So did the conventional fixed income unit trust's investment perfomance which was stable enough. Eventhough, its investment perfomance percentage lower thansharia. The conventional fixed income unit trust liquidity also capable enough, though the redemption wave much happened on this unit trust.Keywords: Redemption moment, Sharia unit trust, Coventional unit trust, Net Asset Value per Unit, New Net Cash Flow.